1989
DOI: 10.1590/s0036-46651989000200004
|View full text |Cite
|
Sign up to set email alerts
|

Acidentes ofidicos causados por Bothrops moojeni: correlação do quadro clínico com o tamanho da serpente

Abstract: RESUMODurante um período de 19 meses (março 1986 a setembro 1987) foram estudados 22 casos de acidentes ofídicos causados por Bothrops moojeni na região de São José do Rio Preto, São Paulo, nos quais o tamanho da serpente foi sistematicamente medido. Foram constituídos dois grupos de pacientes de acordo com o tamanho da serpente: grupo I -9 casos de serpentes pequenas (30 a 53 cm) e grupo II -13 casos de serpentes grandes (80 a 147 cm). Os resultados mostraram: 1. efeitos locais iniciais -dor e edema -mais lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
5

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 3 publications
1
7
0
5
Order By: Relevance
“…However, when dry bites are excluded from the analysis, observation showed that the median SVL of snakes in mild and moderate cases was 40.5cm, while in severe cases it was 99cm. In agreement with these results, other studies with Bothropoides jararaca and Bothrops moojeni showed that accidents caused by juvenile snakes rarely cause severe cases of envenomation 29,30 . Furthermore no statistical difference was verified between the presence of stomach contents and the occurrence of dry bites.…”
Section: Resultssupporting
confidence: 88%
“…However, when dry bites are excluded from the analysis, observation showed that the median SVL of snakes in mild and moderate cases was 40.5cm, while in severe cases it was 99cm. In agreement with these results, other studies with Bothropoides jararaca and Bothrops moojeni showed that accidents caused by juvenile snakes rarely cause severe cases of envenomation 29,30 . Furthermore no statistical difference was verified between the presence of stomach contents and the occurrence of dry bites.…”
Section: Resultssupporting
confidence: 88%
“…O ato de levar o espécime morto ao posto de saúde poderia ajudar a elucidar grande parte desta profusão de nomes locais, podendo ser útil no tratamento clínico do envenenamento. Para algumas espécies do gênero Bothrops ocorre uma variação ontogenética na composição da peçonha (Kouyoumdjian & Polizelli, 1989;Ribeiro & Jorge, 1990;Furtado et al, 1991). Para B. atrox, foram observadas maiores complicações locais e sistêmicas relacionadas ao envenenamento por juvenis desta espécie (Meier, 1986;López-Lozano et al, 2002;Saldarriaga et al, 2003).…”
Section: Altura Das Mordidas (Mm) Quantidade De Mordidasunclassified
“…Para lograr esto las medidas que han demostrado mejores efectos a corto y largo plazo son la inmovilización del miembro afectado, que resulta crucial para aminorar la diseminación del veneno a nivel sistémico (2,5) y la colocación de una ligadura proximal, mas no un torniquete que puede producir una disminución importante del flujo sanguíneo en el miembro afectado aumentando así el riesgo de complicaciones locales en especial por necrosis de los tejidos y alteraciones de coagulación (22,24,25). La aplicación de hielo sobre el sitio de la mordedura al igual que la aplicación de choques eléctricos han demostrado tener efectos perjudiciales en la evolución como infecciones y alteraciones locales de la coagulación (3,5,26,27,28).…”
Section: Discussionunclassified